Gold Price Fluctuation Drives Customers' Gold Installment Investment Decision: Fluktuasi Harga Emas Mendorong Keputusan Investasi Cicil Emas Nasabah - Maysarah, Maysarah; Syafina, Laylan; Nurwani, Nurwani (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Investment decisions are often influenced by macroeconomic variables, among which commodity price fluctuations, such as gold, are prominent. Specific Background: In the context of Islamic banking, Bank Syariah Indonesia (BSI) offers a gold installment product that has seen varied customer responses amidst volatile gold prices. Knowledge Gap: Despite the popularity of gold-based investment products, limited empirical studies address how gold price fluctuations affect customer investment behavior in this specific setting. Aims: This study aims to analyze the extent to which gold price fluctuations influence customer decisions to invest in the gold installment product at BSI KCP Medan A.H Nasution. Results: Using a quantitative method with 71 randomly selected respondents from a population of 250, and applying various statistical tests including hypothesis testing, the findings indicate that gold price fluctuations have a positive and significant effect on investment decisions, with a determination coefficient (R²) of 0.597. Novelty: The study provides empirical evidence linking gold price volatility with investment choices in Islamic gold installment products, a relatively underexplored area. Implications: These results underscore the importance for Islamic financial institutions to monitor gold market dynamics closely, as they significantly shape customer investment decisions. Highlights: Fluctuating gold prices significantly affect customer investment decisions. 59.7% of investment behavior is explained by gold price trends. Study fills a gap in Islamic finance research on gold-based products. Keywords: Gold Price Fluctuation, Investment Decision, Islamic Banking, Gold Installment